2020
DOI: 10.3390/membranes10080185
|View full text |Cite
|
Sign up to set email alerts
|

PVDF-Modified Nafion Membrane for Improved Performance of MFC

Abstract: Low power production and unstable power supply are important bottlenecks restricting the application of microbial fuel cells (MFCs). It is necessary to explore effective methods to improve MFC performance. By using molasses wastewater as fuel, carbon felt as an electrode, and the mixture of K3[Fe(CN)6] and NaCl as a catholyte, an MFC experimental system was set up to study the performance of MFCs with three different proton exchange membranes. A Nafion membrane was used as the basic material, and polyvinyliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…PVA-kC and Nafion have the highest oxygen permeability and lower proton mass transfer compared to VPC and IPC membranes. It has been reported that enhancing the hydrophilicity of the Nafion membrane with PVDF coating decreased the charge-transfer resistance of the MFC as compared to the bare Nafion membrane . Both VPC and IPC have higher water absorptions and can lead to efficient proton conduction through these membranes.…”
Section: Resultsmentioning
confidence: 99%
“…PVA-kC and Nafion have the highest oxygen permeability and lower proton mass transfer compared to VPC and IPC membranes. It has been reported that enhancing the hydrophilicity of the Nafion membrane with PVDF coating decreased the charge-transfer resistance of the MFC as compared to the bare Nafion membrane . Both VPC and IPC have higher water absorptions and can lead to efficient proton conduction through these membranes.…”
Section: Resultsmentioning
confidence: 99%
“…weight. The porosity ( ɛ ) of individual fibers was subsequently calculated utilizing Equation (1) [ 58 , 59 ]. where ɛ is the membrane porosity (%), ρ w is the density of water, M w is the weight of wet membrane, M d is the weight of dry membrane, and V is the volume of the membrane specimen.…”
Section: Methodsmentioning
confidence: 99%
“…weight. The porosity (ε) of individual fibers was subsequently calculated utilizing Equation 1 [58,59].…”
Section: Analysis Of Porositymentioning
confidence: 99%
“…Mediator penukar proton dapat berupa membran atau jembatan garam (salt bridge). Membran penukar proton yang digunakan umumnya adalah nafion (Fan et al, 2020) dan CMI-7000 (Di Palma et al, 2020). Membran tersebut mempunyai harga yang sangat mahal serta harus diimpor.…”
Section: Pendahuluanunclassified